Local high relief at the southern margin of the Andean plateau by 9 Ma: evidence from ignimbritic valley fills and river incision. (20th September 2014) - Montero‐López, Carolina; Strecker, Manfred R.; Schildgen, Taylor F.; Hongn, Fernando; Guzmán, Silvina; Bookhagen, Bodo; Sudo, Masafumi
Abstract A valley‐filling ignimbrite re‐exposed through subsequent river incision at the southern margin of the Andean (Puna) plateau preserves pristine geological evidence of pre‐late Miocene palaeotopography in the north western Argentine Andes. Our new 40Ar/39Ar dating of the Las Papas Ignimbrites yields a plateau age of 9.24 ± 0.03 Ma, indicating valley‐relief and orographic‐barrier conditions comparable to the present‐day. A later infill of Plio–Pleistocene coarse conglomerates has been linked to wetter conditions, but resulted in no additional net incision of the Las Papas valley, considering that the base of the ignimbrite remains unexposed in the valley bottom. Our observations indicate that at least 550 m of local plateau margin relief (and likely >2 km) existed by 9 Ma at the southern Puna margin, which likely aided the efficiency of the orographic barrier to rainfall along the eastern and south eastern flanks of the Puna and causes aridity in the plateau interior.